Reserve Pooling in the Eastern Caribbean Currency Union and the CFA Franc Zone : A Comparative Analysis - Selvon, Hazel (IMF Working Papers; Working Paper ;, 2001)
The paper presents a comparison of the gains from the pooling of reserves, and hence reserve variability, in the Eastern Caribbean Currency Union (ECCU) and the CFA franc zone. The results indicate that countries within the ECCU area have achieved greater balance of payments protection than the CFA zone countries from the pooling of reserves. Unanticipated changes in the terms of trade lowered reserves in the CFA relative to the ECCU, which may reflect a greater reliance on primary commodities in the CFA compared with services in the ECCU.